Peningkatan Kemampuan Membaca Peserta Didik Sekolah Dasar melalui Media Buku Cerita Bergambar - Dede Nurhidayah (Bildung: Jurnal Ilmu Pendidikan, 2026)
Reading ability is a fundamental skill that must be mastered by elementary school students because it serves as the foundation for understanding various subjects. However, in reality many lower-grade students still experience difficulties in reading, such as reading haltingly, mispronouncing words, and having low interest in reading activities. This condition was also found among second-grade students at SDN Timbangnagara, where students showed low reading ability and limited interest in reading. This study aims to improve students’ reading ability through the use of illustrated storybooks. The research employed a Classroom Action Research method using the Kemmis and McTaggart model, which includes planning, action, observation, and reflection stages conducted in two cycles. The research subjects were 18 second-grade students of SDN Timbangnagara. Data were collected through observation, reading ability tests, interviews, and field notes. The data were analyzed using qualitative descriptive analysis and simple quantitative analysis by comparing learning outcomes between cycles. The results showed that the use of illustrated storybooks was able to improve students’ reading ability. The average score increased from 53.89 in the pre-cycle to 65.83 in cycle I and 76.11 in cycle II. In addition, students’ interest and participation in reading activities also improved. Therefore, illustrated storybooks are proven to be an effective medium for improving the reading ability of second-grade elementary school students.